CD20 expression: A risk stratification factor for newly diagnosed multiple myeloma with t(11;14) - Jian, Yuan; Zhang, Zhiyao; Zhou, Huixing; Yang, Guangzhong; Geng, Chuanying; Wang, Huijuan; Gao, Wen; Chen, Wenming (Frontiers in Oncology, 2022)
Translocation (11;14) is one of the most frequent recurrent cytogenetic abnormalities in multiple myeloma (MM), while its clinical prognostic value remains controversial. CD20 expression is uncommon in MM while strongly associated with t(11;14). To investigate whether CD20 could provide further prognostic value in MM patients harboring t(11;14), we retrospectively analyzed CD20 expression detected by flow cytometry in 211 newly diagnosed MM patients with t(11;14). The clinical characteristics and outcomes were analyzed between CD20 positive and negative patients. According to our results, CD20 expression was found in 34.6% (73/211) newly diagnosed MM (NDMM) patients with t(11;14), associated with lower serum creatine levels and lower incidence of plasmacytoma. Based on similar treatment regimens, CD20 positive patients had a comparable overall response rate to CD20 negative patients, whereas had a lower CR/sCR (complete response/ stringent complete response) rate than the latter (31.4% vs. 46.4%, P =0.045). Nevertheless, CD20 positive patients had a longer tendency of progression-free survival (PFS) (59.0 vs. 29.0 months, P =0.163) and significantly longer overall survival (OS) (99.0 vs. 56.0 months, P=0.003) than CD20 negative patients. Further investigation among CD20 expression proportion showed that strong expression of CD20 (>80% of bone marrow plasma cells) exhibited the longest OS (median not reached, P =0.011). However, the favorable impact of CD20 expression on survival was eliminated with the contaminant presence of cytogenetic abnormalities besides t(11;14). Autologous stem cell transplantation (ASCT) could improve the prognosis of CD20 negative t(11;14) patients. Multivariate analysis confirmed that CD20 expression was an independent favorable indicator for longer OS in t(11;14) MM patients. In conclusion, CD20 expression is a favorable prognostic factor in NDMM with t(11;14) and could provide further risk-stratification value in this heterogeneous disease subgroup.